Semisynthesis of 5-O-ester derivatives of renieramycin T and their cytotoxicity against non-small-cell lung cancer cell lines - Koonchira Buaban; Bhurichaya Innets; Korrakod Petsri; Suwimon Sinsook; Pithi Chanvorachote; Chaisak Chansriniyom; Khanit Suwanborirux; Masashi Yokoya; Naoki Saito; Supakarn Chamni (Scientific Reports, 2023)
Abstract The semisynthesis of 5-O-ester derivatives of renieramycin T was accomplished through the photoredox reaction of renieramycin M (1), a bistetrahydroisoquinolinequinone alkaloid isolated from the Thai blue sponge Xestospongia sp. This process led to the conversion of compound 1 to renieramycin T (2), which was subsequently subjected to Steglich esterification with appropriate acylating agents containing linear alkyl, N-tert-butoxycarbonyl-L-amino, and heterocyclic aromatic substituent. Notably, the one-pot transformation, combining the photoredox reaction and esterification led to the formation of 7-O-ester derivatives of renieramycin S due to hydrolysis. Subsequently, the in vitro cytotoxicity of the 17 semisynthesized derivatives against human non-small-cell lung cancer (NSCLC) cells in parallel with normal cell lines was evaluated. Among the tested compounds, 5-O-(3-propanoyl) ester of renieramycin T (3b) exhibited potent cytotoxic activity with half-maximal inhibitory concentration (IC50) values at 33.44 and 33.88 nM against H292 and H460 cell lines, respectively. These values were within the same range as compound 1 (IC50 = 34.43 and 35.63 nM) and displayed twofold higher cytotoxicity compared to compound 2 (IC50 = 72.85 and 83.95 nM). The steric characteristics and aromatic orientation of the 5-O-ester substituents played significant roles in their cytotoxicity. Notably, derivative 3b induced apoptosis with minimal necrosis, in contrast to the parental compound 1. Hence, the relationship between the structure and cytotoxicity of renieramycin–ecteinascidin hybrid alkaloids was investigated. This study emphasizes the potential of the series of 5-O-ester derivatives of renieramycin T as promising leads for the further development of potential anti-NSCLC agents.